Japanese computer-aided learning package / Siti Nur Hidayah Johar - Siti Nur Hidayah , Johar (2005)
NihonGo, a Japanese learning software, is developed to teach the basic Japanese language to the public in an easy way. It comprises 8 modules. They arc Maintenance,Writing, Lessons, Exercises, Quizzes, Games, Karaoke and Dictionary. It is a bilingual system that provides text-to-speech synthesizers (English, Malay and Japanese) and instructions in either English or Malay.The NihonGo's administrator can updates and add new terms, or delete existing terms in Maintenance module. Learners choose the topics to study in Lessons module. As to make sure they understand Japanese language grammars, they have to do exercises and quizzes. Games and Karaoke provides learning in a fun way and keep the learners relax. Dictionary allows the learners to search the definition of a Japanese word term. NihonGo was developed using incremental evolution through rapid prototyping technique. The development tool used include Visual Basic.NET, Microsoft Access 2003, Adobe Photoshop CS, and Macromedia Flash MX 2004 and so on. The NihonGo package can be used as a learning tool in schools. It i beneficial for organization that want to instill learning Japanese language in an easy and fun way.Therefore, it also promote the Japanese culture, through interesting multimedia NihonGo can attract the learners and thus enhance their learning processes.